Panorama 1981 - Baptiste, Ronald (Daily Express)
A Ronald Baptiste's picture of Phase II Pan Groove on stage with the jampacked North Stand in the background as Panorama 1981 got underway at the Queen's Park Savannah.
Keywords: Steel bands (Music) -- Competitions -- Trinidad and Tobago; Panorama (Musical festival); Steel band music -- Trinidad and Tobago